Evaluation of a scoring system for predicting lymph node malignancy in ultrasound guided fine needle aspiration practice. Issue 12 (10th June 2011) - Wu, Maoxin; Chen, Hua; Zheng, XiaoYong; Burstein, David E.; Aisner, Dara
<x xml:space="preserve">Abstract</x> Ultrasound‐guided fine needle aspiration (USG‐FNA) has enabled cytopathologists to accurately diagnose smaller or non‐palpable lymph nodes (LN) on a regular basis. Pre‐FNA clinical and ultrasonographic factors, such as a patient's age, ratio of short to long axis diameter (S/L ratio), internal echogenicity, and the vascular pattern of a LN, are reported to be able to predict the benign or malignant nature of a LN. This study is designed to test the formula "0.06 × (age) + 4.76 × (S/L ratio) + 2.15 × (internal echo) + 1.80 × (vascular pattern)" generated from the study of Liao et al. as a scoring system for predicting LN malignancy in a cytopathologist operated USG‐FNA practice. Eighty‐three reports of USG‐FNA of LNs issued between 7/1/2008 and 4/28/2010 were reviewed. Patient's age, S/L ratio, internal echo, and vascular pattern were used to generate scores based on the aforementioned formula. A score of seven was used as a cutoff for predicting benign (<7) and malignant (>7) LNs. FNA cytology diagnosis, flow cytometric analysis as well as subsequent surgical diagnosis in some cases served as gold standard for statistical analysis. Among 46 USG‐FNA of LNs with scores > 7, 38 were malignant and eight were benign. All 37 USG‐FNA of LNs with scores < 7 were proven to be benign. The scoring system achieved 100% sensitivity, 82% specificity, 83% positive predictive value, 100% negative predictive value, and 90% accuracy. Further study of the eight "false‐positive" cases revealed that three of them (37.5%) were found to be malignant in follow‐up FNA and/or surgical biopsy. This scoring system may serve as a complementary tool in determining how aggressive a FNA procedure should be performed, how a FNA sample of LN should be triaged for ancillary study, and how closely a patient with lymphadenopathy should be followed up. Diagn. Cytopathol. 2013;41:1100–1106. © 2011 Wiley Periodicals, Inc.